2007
DOI: 10.2217/14622416.8.7.713
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in the VKORC1 Gene Polymorphism and an Association with Warfarin Dosage Requirements in Cardiovascular Surgery Patients

Abstract: The frequencies of the intron 1 VKORC1 1173 T>C SNP show significant differences between ethnic groups and are associated with warfarin dose requirements for achieving a recommended International Normalized Ratio range in Japanese cardiovascular surgery patients. This study supports the example of warfarin as an appropriate model for applying personalized medicine for anticoagulant drugs, and highlights the importance of ethnicity in pharmacogenetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…Furthermore, the TT variant homozygote type of VKORC1 occurs in approximately 80% of Japanese, with very few Japanese having the wild type (CC type), whereas 27% of Israeli bear the TT type. 15) In the present study, the frequencies of the CYP2C9 *2 , CYP2C9 *3 and VKORC1 SNPs were similar.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Furthermore, the TT variant homozygote type of VKORC1 occurs in approximately 80% of Japanese, with very few Japanese having the wild type (CC type), whereas 27% of Israeli bear the TT type. 15) In the present study, the frequencies of the CYP2C9 *2 , CYP2C9 *3 and VKORC1 SNPs were similar.…”
Section: Discussionsupporting
confidence: 69%
“…15) Fluorescent dye terminator cycle sequencing was performed with the same primers used for the PCR amplifications; the data were analyzed using an auto-sequencer (model 377KL, Applied Biosystems, Foster City, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the AJ CYP2C9 extensive, intermediate, and poor metabolizer frequencies were 62%, 33%, and 5%, and the VKORC1 c.−1639 G/G, G/A, and A/A frequencies were 29%, 48%, and 23%, respectively [38]. Related studies have identified distinct CYP2C9 ( *2 and *3 ) and VKORC1 c.174-136C>T (1173C>T) frequencies between Israeli Jewish (AJ, Yemenite, Moroccan, and Libyan) and Japanese individuals [68, 69]. Given the paucity of CYP2C9 full gene sequencing studies among Jewish individuals, it is currently unknown if unique CYP2C9 variant alleles exist in this population, suggesting further studies are warranted.…”
Section: Jewish Pharmacogeneticsmentioning
confidence: 99%
“…The incorporation of the CYP2C9 * 8 allele into a pharmacogenetic dosing algorithm increases accuracy in African–Americans [61]. The population frequencies of the −1639 A allele indicating haplotype A are remarkably different across populations and reported as 75–92% in East Asians [19,55,63,64], 35–47% in Europeans [56,60,65,66], 9–12% in African–Americans [19,29,48,61] and 29–48% in mixed populations [19,39]. The pronounced disparity in haplotype A frequency explains, in part, why mean effective warfarin dose is often lower in East Asian [67,68] and higher in African compared with Caucasian populations [48].…”
Section: Prediction Of Warfarin Responsivenessmentioning
confidence: 99%